Pengaruh Influencer Dan Literasi Keuangan Terhadap Minat Investasi Mahasiswa - Trisnaningsih Trisnaningsih; Sihabudin .Sihabudin; Robby Fauji (Journal of Business and Economics Research (JBE), 2022)
The capital market has a big role in the economy, some of these functions are as a means for companies to seek capital and also as an investment instrument for the community. In college, materials are usually taught about the capital market and other financial institutions. Therefore, students are considered to have sufficient financial literacy so that students can invest. However, the number of FEB students recorded in 2020 was 2038 people, while students who had RDN were only 49 people or 2.40% of the total FEB students. The analysis technique used in this research is multiple regression analysis, the sampling technique used is purposive sampling. with the desired respondent criteria in this study, including: 1. Active students of FEB UBPK; 2. Class of 2018, 2019, and 2020 students; and 3. Students who already have personal income. Based on the results of research conducted that the significance value of the influencer variable is 0.000 < 0.05 and the financial literacy variable has a significant value of 0.000 < 0.005. it can be concluded that the two variables have a significant positive effect on investment interest. Then simultaneously financial literacy variables and influencers have a significant effect on student investment interest.